The Significance of Vaccines in Mitigating Emerging Infectious Diseases: A Comprehensive Review - ALNAKHLI, REHAB HUSSAIN; NAGEI , SHARIFAH HADI AHMAD; Alotaibi , Adel Shabib; ATAIFI, HAYAT IBRAHIM YAHYA; ALMUTAIRI, MUTEB BIN KHALID BIN HAMAD; Al Mutairi, Muteb Saleem; Ghashum, Rahma Qasem Ajibi; alhakami, bashaer abdulaziz; Hakimi, Amal Jadah Abu Al-Qasim; Alshammari, Salman Hamoud; sahely, Rokaia Abdu; sahely, Mariam Abdu; et al. (Journal of Ecohumanism, 2024)
Background: The global rise in emerging infectious diseases presents significant challenges to public health, exacerbated by issues such as antimicrobial resistance (AMR). Vaccination remains a pivotal strategy in preventing the spread of these diseases, yet its role is often underappreciated in the context of rising drug resistance. Methods: This review synthesizes current literature on the effectiveness of vaccines and immunotherapeutic approaches in controlling emerging infectious diseases. It analyzes data from clinical studies, epidemiological reports, and the impact of vaccination on AMR trends, particularly in regions severely affected by infectious diseases. Results: Findings indicate that vaccines significantly reduce the incidence and severity of diseases such as tuberculosis, malaria, and COVID-19. Furthermore, immunotherapy, including monoclonal antibodies, demonstrates potential in enhancing host immunity against multidrug-resistant pathogens. Despite advancements, the ongoing rise of AMR, particularly in low- and middle-income countries, poses a considerable threat to the efficacy of existing vaccines and treatments. Conclusion: Vaccination and immunotherapeutic strategies are essential components in the fight against emerging infectious diseases and AMR. Continued investment in vaccine development and implementation is critical to mitigate the impact of these evolving health threats. Future research should focus on innovative vaccine technologies and strategies to enhance public health responses in vulnerable populations.